Foxp3 Reprograms T Cell Metabolism to Function in Low-Glucose, High-Lactate Environments - Angelin, Alessia; Gil-de-Gómez, Luis; Dahiya, Satinder; Jiao, Jing; Guo, Lili; Levine, Matthew H; Wang, Zhonglin; Quinn, 3rd, William J; Kopinski, Piotr K; Wang, Liqing; Akimova, Tatiana; Liu, Yujie; et al. (Cell metabolism, 2017)
Immune cells function in diverse metabolic environments. Tissues with low glucose and high lactate concentrations, such as the intestinal tract or ischemic tissues, frequently require immune responses to be more pro-tolerant, avoiding unwanted reactions against self-antigens or commensal bacteria. T-regulatory cells (Tregs) maintain peripheral tolerance, but how Tregs function in low-glucose, lactate-rich environments is unknown. We report that the Treg transcription factor Foxp3 reprograms T cell metabolism by suppressing Myc and glycolysis, enhancing oxidative phosphorylation, and increasing nicotinamide adenine dinucleotide oxidation. These adaptations allow Tregs a metabolic advantage in low-glucose, lactate-rich environments; they resist lactate-mediated suppression of T cell function and proliferation. This metabolic phenotype may explain how Tregs promote peripheral immune tolerance during tissue injury but also how cancer cells evade immune destruction in the tumor microenvironment. Understanding Treg metabolism may therefore lead to novel approaches for selective immune modulation in cancer and autoimmune diseases.